Bitcoin's Sharia Legitimacy: Strength Analysis and Implications as a Financial Transaction Tool - Labibunnajah, Muhammad Hilmi; Al Muzakky, Alamul Huda; Lutfiyah, Lutfiyah (Tasharruf: Journal Economics and Business of Islam, 2024)
This study seeks to reconcile the conflicting viewpoints on Bitcoin by offering a Shariah-based perspective, utilizing contemporary interpretations of Quranic verses, fiqh principles, and hadith to demonstrate Bitcoin's supremacy as a currency. This study used a qualitative approach combined with normative analysis, interdisciplinary perspectives (economics and Islamic law), and a descriptive-comparative method based on David Ricardo's theory of comparative advantage to assess Bitcoin's legitimacy as a medium of exchange in Islamic economic contexts. These methodologies enable the research to address the core questions holistically, considering economic, legal, and ethical dimensions. The findings indicate that Bitcoin has attributes similar to gold, such as scarcity, divisibility, mobility, and durability, making it a suitable store of value. While institutes such as MUI and LBM NU East Java classified Bitcoin as haram owing to ambiguity, harm, and speculation, the study contends that with correct understanding, Bitcoin may be lawful under fiqh principles. Blockchain transparency reduces dharar and manipulation, providing an ethical alternative to fiat currency. Furthermore, Bitcoin's intrinsic worth is consistent with Islamic financial principles, as opposed to fiat currency's inflation and value depreciation. The researcher finds that understanding the foundations of Bitcoin can help consumers reduce gharar (uncertainty), dharar (harm), and speculation. Blockchain technology ensures transparency, prevents manipulation and abuse, and, like traditional currencies, allows for price formation based on supply and demand. These attributes highlight Bitcoin's potential as a Sharia-compliant medium of exchange that addresses fiat currency limits while also providing inflation protection.